Incentive policies for prefabrication implementation of real estate enterprises: An evolutionary game theory-based analysis. (September 2021) - Wang, Jun; Qin, Yanjun; Zhou, Jingyang
Abstract: Prefabrication construction method has been considered an effective way for enhancing the environmental performance and sustainable development of the construction industry. Many countries have imposed policies to stimulate the implementation of prefabrication. However, the efficiency of the incentive policies in China did not turn out as expected because of the existing benefit game between real estate enterprises and the government under the influence of consumers' purchasing intention. An evolutionary game model was established on the basis of 16 variables influencing the strategy selection of game players for determining the effective incentive policies. The interaction effect of the two players' behaviours was discussed. Four probable scenarios of evolutionary stable strategy (ESS) exist in the game. However, the probabilities of "Incentive" from the government and "Implement" from real estate enterprises depend on the values of the 16 variables. The simulation of the evolutionary system was conducted to analyze the critical variables influencing the game. The increase of reputational incentives, financial incentives, the acceptance level of consumers and penalty and the reduction of additional costs can speed up the achievement of ESS between the government and real estate enterprises. Incentive policies should focus not only on real estate enterprises but also on consumers, manufacturers of prefabricated components and contractors. Highlights: Revealing influences of incentive policies on prefabrication implementation. The evolutionary game between government, real estate enterprises and consumers. Emphases on a policy mix of financial and reputational incentives and penalties. Four policy recommendations for prefabrication implementation were presented.